Adaptive output tracking for nonlinear infinite-dimensional systems. Issue 26 (2022) - Hastir, A.; Winkin, J.J.; Dochain, D.
Abstract: An adaptive model-free funnel controller is presented for the output tracking of a general class of input-output (nonlinear) systems, which may encompass systems with possibly infinite-dimensional internal dynamics. After describing the system class and the related assumptions, the main result states that funnel control is well-adapted for a general class of semilinear infinite-dimensional systems with globally Lipschitz nonlinearity, by using a decomposition of the state space based on the existing Byrnes-Isidori form. Standard assumptions are stated, and in particular the Bounded Input State Bounded Output (BISBO) stability of the nonlinear infinite-dimensional system. A way of getting this assumption is presented too. The theoretical results are applied on a damped sine-Gordon equation and illustrated by means of numerical simulations.